The Effect of Psychology, Organizational Culture and Motivation on Employee Performance: The Case of PT Bumi Andalas Permai - Prayoga, Yongki; Idris, Muhammad; Trihandayani, Zaleha (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This research aims to determine the influence of psychological factors, organizational culture and motivation on employee performance at PT. Bumi Andalas Permai. This type of research is associative. The variables researchers use are psychological factors, organizational culture, work motivation and performance. The sample in this research was employees of PT. Bumi Andalas Permai is located in the Simpang Heran River - Beyuku II River Forest Group, OKI Regency, South Sumatra Province, with 117 people selected using cluster sampling. The data used in this research is primary data collected through a questionnaire. The data analysis technique used is Multiple Linear Regression. The results of this research show that (1) psychological factors, organizational culture, and motivation have a positive and significant effect on employee performance, (2) psychological factors have a positive and significant effect on employee performance, (3) organizational culture has a positive and significant effect on employee performance, (4) motivation has no significant effect on employee work motivation